An experimental study on the effect of air-assist and wall-flow distribution in the spark ignition engine performance - Abu Bakar, Rosli; Lee, Chang Saik; Chon, Mun Soo (Faculty of Mechanical Engineering, 1996)
The purpose of this paper is to present the investigation on the role of the spray characteristics and wall-flow distribution that influenced the subsequent process such as mixture formation, combustion and exhaust emission in gasoine engine. In this study, the effect of the assistant air pressure on the spray formation and atomization was analysed and an air-assist fuel injection adapter was developed to investigate the spray characteristics as well as to measure the wall-flow distribution.